EVALUASI KEBIJAKAN SUMATIF AKHIR SEMESTER (SAS) BERBASIS DIGITAL: STUDI PADA SISWA TINGKAT PENDIDIKAN MENENGAH: Penilaian Digital, Pendidikan Menengah, Sumatif Akhir Semester - Syarif Hidayatullah Z; Dina Hermina; Nuril Huda (IAI DARUL ULUM KANDANGAN, 2025)
Abstract: This study aims to evaluate the implementation of digital-based summative final assessment policy using Google Forms at the secondary education level. The research focuses on identifying students self-confidence, anxiety, belief, time management, and technological comfort during digital-based assessments. Employing a quantitative research method with descriptive statistical analysis techniques, the findings reveal that students adapt well to digital assessments, though they still require a guidance and psychological support enhancement in undergoing digital-based evaluations.